2013
DOI: 10.1111/and.12156
|View full text |Cite
|
Sign up to set email alerts
|

Total globozoospermia associated with increased frequency of immature spermatozoa with chromatin defects and aneuploidy: a case report

Abstract: Globozoospermia, characterised by the presence of round spermatozoa lacking acrosomes in an ejaculate, is a known cause of male infertility. Semen analysis, including sperm chromatin structure assay, toluidine blue, chromomycin A3 and aniline blue staining and fluorescence in situ hybridisation, was performed in an infertile globozoospermic patient to establish to which extent these genetic factors contributed to his infertility. No spermatozoa capable of hyaluronan (HA) binding were detected in the HA binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
6
27
0
Order By: Relevance
“…We found a statistically significant difference in total aneuploidy rate between globozoospermic men and controls. This result is consistent with previous studies (Perrin et al, ; Vozdova et al, ) showing an increased aneuploidy frequency like Perrin et al () who found a high rate of aneuploidy in 46% of the patients compared to controls. Controversial results were obtained, and some studies have found no relationship between globozoospermia and sperm chromosomal abnormalities (Viville et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…We found a statistically significant difference in total aneuploidy rate between globozoospermic men and controls. This result is consistent with previous studies (Perrin et al, ; Vozdova et al, ) showing an increased aneuploidy frequency like Perrin et al () who found a high rate of aneuploidy in 46% of the patients compared to controls. Controversial results were obtained, and some studies have found no relationship between globozoospermia and sperm chromosomal abnormalities (Viville et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, different groups have assessed chromatin condensation, chromosomal aneuploidy and DNA damage in globozoospermia (Brahem, Mehdi et al., ; Brahem, Elghezal et al.,; Carrell et al.,; De Braekeleer et al., ; Deemeh et al.,; Perrin et al., ; Vozdova et al., ; Yassine et al., ). In contrary to some studies (Brahem, Elghezal et al., ; De Braekeleer et al., ), other studies have showed high level of protamine deficiency, DNA damage and aneuploidy in these cases (Brahem, Mehdi et al., ; Carrell et al.,; Deemeh et al.,; Perrin et al., ; Vozdova et al., ; Yassine et al., ). This difference may account for low fertilisation and poor embryo development in cases in which AOA was applied following ICSI (Check et al., ; Rybouchkin et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several studies have investigate that failure in pregnancy rate following assisted reproduction technique (ART) and suggest it may be related to sperm DNA fragmentation related to apoptosis, abnormal sperm chromatin remodelling and oxidative stress, (Osman, Alsomait, Seshadri, El‐Toukhy, & Khalaf, ; Tandara et al., ; Zhao, Zhang, Wang, & Li, ). In this regard, previous studies have demonstrated that percentage of fragmented DNA and also aneuploidies in spermatozoa of men affected by globozoospermia were significantly higher than normal spermatozoa in a few cases (Brahem, Mehdi, Elghezal, & Saad, ; Perrin et al., , ; Vicari et al., ; Vozdova et al., ). In addition, abnormal chromatin condensation, low levels of protamines (P1 and P2) and high level of nuclear histones were reported in these individuals as well (Carrell, Emery, & Liu,; Deemeh, Tavalee, Razavi, & Nasr‐ Esfahani,; Vozdova et al., ; Yassine et al., ).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is exposed that globozoospermia as well as other irregular morphologic shapes of human spermatozoa is coupled with DNA strand breaks and abnormal chromatin configures. Though several studies have exposed no momentous amplification in DNA denaturation or sperm DNA disintegration in globozoospermic cases compared productive men [11][12][13]. Sutovsky et al, in 2001 with the preface of SUTI (sperm-ubiquitin tag immunoassay) practice demonstrated that globozoospermic are extremely ubiquitinated that pointed their injured DNA [14].…”
Section: Casementioning
confidence: 99%